CLASSIFICATION OF BIS-CARBAMATES OF THE MEE SERIES BASED ON THE NOMENCLATURE OF GOODS OF FOREIGN ECONOMIC ACTIVITY OF THE REPUBLIC OF UZBEKISTAN - E.E. Mashaev; I.R. Asqarov; M.M. Xojimatov; M.M. Muminjonov (Journal of new century innovations, 2023)
Abstract. In this work, the reagents and main products, which are raw materials for the bis-carbamates synthesized by the authors, are classified based on the nomenclature of goods in foreign economic activity (NFEA). By them, plants based on N,N'-hexamethylene bis-[(o,m-cresolyl)]-carbamate and its derivatives are assigned to the code 3838 93 900 1, group 38 of NFEA, class 3808, code 3838 93 900 1 as growth regulators and code 3838, after receiving a certificate of compliance with the MEE series of substances synthesized by us as a commodity, it was named “MaXstim”, and an offer was made to include this drug in the NFEA.